Analysis of Antidepressant Activity of Huang-Lian Jie-Du Decoction Through Network Pharmacology and Metabolomics - Qu, Shu-Yue; Li, Xiao-Yue; Heng, Xia; Qi, Yi-Yu; Ge, Ping-Yuan; Ni, Sai-jia; Yao, Zeng-Ying; Guo, Rui; Yang, Nian-Yun; Cao, Yi; Zhang, Qi-Chun; Zhu, Hua-Xu (Frontiers in Pharmacology, 2021)
Depressive disorder is a common mental disorder and is characterized by depressed mood and loss of interest or pleasure. As the Herbal drugs are mainly used as complementary and alternative therapy for depression. This study aimed at exploring antidepressant activity of Huang-lian Jie-du Decoction (HLJDD), a traditional Chinese medicine formula. In addition, we evaluated active components of the formula and potential depression-associated targets. HLJDD was administered on chronic unpredictable mild stress-induced (CUMS) depressive mice. Antidepressant effects of HLJDD were investigated through force swimming test (FST), novelty-suppressed feeding test (NSF), and open field test (OFT). Active components of HLJDD, potential targets, and metabolic pathways involved in depression were explored through systemic biology-based network pharmacology assay, molecular docking and metabolomics. FST results showed that CUMS mice administered with HLJDD had significantly shorter immobility time compared with mice in the control group. Further, HLJDD alleviated feeding latency as shown by NSF results whereas OFT results showed that HLJDD increased moving distance and duration for CUMS mice. Thirty-eight active compounds in HLJDD were identified based on drug-like characteristics, and pharmacokinetics and pharmacodynamics profiles. Moreover, forty-eight molecular targets and ten biochemical pathways were identified through molecular docking and metabolomics. GRIN2B, DRD, PRKCA, HTR, MAOA, SLC6A4, GRIN2A and CACNA1A targets are implicated in inhibition of depressive symptoms through modulation of tryptophan metabolism, serotonergic and dopaminergic synaptic activities, cAMP signaling pathway, and calcium signaling pathway. Further pharmacology-based analysis showed a correlation between HLJDD and tryptophan metabolism. A total of thirty-seven active compounds, seventy-six targets, and sixteen biochemical pathways were involved in tryptophan metabolism. These findings show that HLJDD acts on targets such as SLC6A4, HTR, INS, MAO, CAT and FoxO, PI3K/Akt, calcium, HIF-1, and mTOR signaling pathways, and modulates serotoninergic and dopaminergic synaptic functions. In addition, metabolomics showed that tryptophan metabolism is a main target for HLJDD in CUMS mice. The findings of the study show that HLJDD has antidepressant effects. SLC6A4 and MAOA targets in tryptophan metabolism were inhibited by berberine, baicalein, tetrahydroberberine, candicine and may be the main antidepressant targets for HLJDD.